PENGARUH DESAIN AKTIVITAS LABORATORIUM INKUIRI TERBIMBING TERHADAP PENGUASAAN KONSEP FISIKA DAN KETERAMPILAN PROSES SAINS SISWA SMAN 7 MATARAM - Wardani, Intan Kusuma (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2014)
Actually learning physics can not be separated from learning science . Learning science is to understand natural phenomena and the nature of science by inquiry and discovery . The statement indicates that not only the mastery of physics concepts that should be good , but students also need to know how the concept was found . The purpose of this study was to determine the effect of guided inquiry labs to mastery of physics concepts and science process skills of students . This study was a quasi -experiment using two classes of experimental class and control class . Experimental class is a class that is taught using guided inquiry labs and control class is a class that is studying the use of laboratory verification . The research was conducted on the subject of fluid . The population in this study were all class XI Science SMAN 7 Mataram in the second semester of academic year 2013/2014 . Samples were taken in a random way and obtained class - XI IPA 1 as the control class and class XI - IPA 5 as a class experiment . Data were analyzed using multivariate analyzes of ANOVA . The results of the analysis yields that the research hypothesis is accepted . The results of the analysis and discussion showed that students who learn with guided inquiry labs have mastery of physics concepts and science process skills better than students who studied with laboratory verification. Keywords: Design of guided inquiry lab activity, mastery of concepts, science process skills.